Low-dose tryptophan depletion in recovered depressed patients induces changes in cognitive processing without depressive symptoms - Hayward, G; Goodwin, G; Cowen, P; Harmer, C (Elsevier, 2005)
Background: Acute tryptophan depletion can induce a transient reappearance of depressive symptoms in recovered depressed patients. The neurochemical mechanism if thought to be impairment of brain serotonin neurotransmission, but the neuropsychologic mechanisms underlying the effect are unclear. Methods: To assess whether low-dose tryptophan depletion can tease out the psychological mechanisms sensitive to substrate depletion in vulnerable subjects without inducing mood changes, a between-subjets randomized design was used. Recovered depressed patients (n=24) and healthy volunteers (n=24) were administered white fasting either a tryptophan-free or a control mixture, containing 31.2 and 33.2 g of amino acids, respectively. Objective and subjective rating of mood were made before and 5 hours after ingestion; at the latter time point, cognitive and emotional processing were also assessed. Results: Low-dose tryptophan depletion did not affect mood. Significant changes in emotional and cognitive processing occurred in the recovered depressed group, however, and to a lesser extent in the healthy volunteers. The profile of effects seen in the recovered patients suggested a return of the impairments seen in acute depression. Conclusions: Our data suggest that low-dose tryptophan depletion permits investigation of the cognitive correlates of acute reductions in brain serotonin in populations vulnerable to depression and in healthy volunteers, without causing depressive symptoms.